An analysis of factors affecting the speed of establishment of field-based farmer learning alliances: A case of Farmer Learning Centres (FLCs) in southern Zimbabwe. Issue 1 (2nd January 2022) - Mapangisana, Toga; Mapfumo, Paul; Siziba, Shephard; Mtambanengwe, Florence
Abstract : Farmer learning alliances are an important vehicle for information dissemination and co-innovation among smallholder communities in southern Africa. However, the process of establishing functional farmer learning alliances tends to be uneven, slow, and costly for many development agents. This study explored factors that can be used to account for the unevenness in the speed of establishment of Farmer Learning Centres (FLCs). Twenty FLCs were initiated in Beitbridge District, southern Zimbabwe, and monitored over two years. Three categories of FLCs were observed in terms of time taken to reach maturity and full functionality: Slow, Medium, and Fast. Discriminant analysis was used to identify significant discriminatory factors among the three FLC categories. Results indicated that the number of meetings attended, the main source of livelihoods, age, sex, marital status, and years of formal education of the household head, and support from local leaders, differentially accounted for the speed of FLC establishment. The study recommends that learning alliances should be introduced through extension and local leaders as they are key information disseminators and custodians of local resources, and enterprise-specific training should be done to encourage full commitment to learning alliances to foster quicker establishment.